KAJIAN DESKRIPTIF KESEHATAN MENTAL MASYARAKAT DESA WAQ TOWEREN BERDASARKAN SKRINING SRQ DAN SDQ MELALUI PROGRAM SUARA HATI DESA - M. Syukri Rizki Hamdalah; Fitdaturrahmi Fitdaturrahmi; Tanty Rizky Soripada; M. Dhuha Masyuhri; Dinnisa Naura Yasmin; Muhammad Syahru; Amelia Zahra; Rizky Ananda Putri; Nadiyatul Rahima Sinaga; Neiva Zaida Hasanah Saragih (LPPM STAI Muhammadiyah Probolinggo, 2026)
Mental health is an important part of community welfare, but data related to the mental health conditions of village communities is still limited. This study aims to describe the mental health condition of the people of Waq Toweren Village based on the results of the Strengths and Difficulties Questionnaire (SDQ) screening in adolescents and the Self Reporting Questionnaire (SRQ) in adults through the Village Voice of the Village Program. This study used a descriptive quantitative approach with respondents of 17 adolescents and 17 adults, respectively. Data was collected through SDQ and SRQ questionnaires, then analyzed using descriptive statistics to see the distribution and tendencies of respondents' answers. The results of the study showed that adolescents experienced psychosocial difficulties at a mild to moderate level with the strength of social behavior that was still quite good. Meanwhile, the adult community has an average SRQ score of 5.6 which is close to the threshold of mental emotional disorders. This study provides basic data as an initial mapping of the mental health conditions of village communities and can be used as a reference in planning community-based mental health assistance programs.